Cryogenic broadband vibration measurement on a cryogen-free dilution refrigerator. (March 2019) - Schmoranzer, D.; Luck, A.; Collin, E.; Fefferman, A.
Highlights: Vibration measurements up to 50 kHz performed on a dry dilution refrigerator. Room temperature accelerometry at the top flange and cryogenic measurements at the mixing chamber plate. Dominant contribution in terms of acceleration is found, surprisingly, near 20 kHz. Practical measures that improve the vibration levels were tested. Abstract: This manuscript reports a set of acceleration measurements in the frequency range from 0 to 50 kHz performed at the mixing chamber plate (2 axes) and the top flange (3 axes) of a cryogen-free dilution refrigerator. Various configurations of the support frame and coupling to the pulse tube compressor and motor have been tested, and the dominant contribution in the spectrum of vibrations is located, surprisingly, near 20 kHz. Finally, the efficiency of various precautions in suppressing the observed vibration levels is illustrated.